Evaluation of the Western Cape Province Developmental Screening Programme - Michelson, Lori (Department of Paediatrics and Child Health, 2023)
This study evaluates the input, process and output parameters of the Western Cape Developmental Screening Programme in order to inform policy and practice regarding developmental screening in the province. The study describes the background, development and implementation of the screening programme and examines its current delivery, including the main enabling factors and barriers to implementation. In order to achieve the abovementioned objectives, a combination of predominantly qualitative and some quantitative data was gathered in stages from all levels of the health system (provincial, regional and district levels) using a number of different methods. In addition to documentary and literature reviews, information was gathered via structured interviews with key health managers at a provincial and regional level, a rapid facility survey and facility based assessments. Information gathered from interviews and focus groups was analysed thematically, while rapid facility survey results were analysed via Epilnfo. Despite numerous successes in its development and the overall awareness of the Developmental Screening Programme, developmental screening is not conducted uniformly across the province. Almost a quarter of primary health care facilities do not deliver any aspect of the programme and only one of nine facilities deliver according to protocol. This study concludes that despite the Developmental Screening Programme being a well-conceptualised and highly valued programme, its delivery has failed as a result of constraints within the broader health system. As previous evaluations of child health programmes have demonstrated, the overall transformation of the health system, organisation of service delivery at a primary health care level and gaps in human resource development and information systems impact significantly on the delivery of preventive service delivery for children. As official programmes for developmental screening are not conducted in any other provinces, the study results may also inform policy and practice on a national level.